Reinvestigating social vulnerability from the perspective of Critical Disaster Studies (CDS): directions, opportunities and challenges in Aotearoa disaster research - Shinya Uekusa; Matthew Wynyard; Steve Matthewman (Kōtuitui)
This article argues that resilience has been overemphasised in popular and scholarly discourse, while social vulnerability has been comparatively overlooked. We therefore need to shift the focus from resilience and adaptation towards vulnerability and the various structures that engender and maintain systemic inequality and disadvantage. This necessitates a shift from strict hazard management and resilience building to considerations of social justice. People should not have to be resilient to ongoing marginalisation and stigmatisation, and, in focusing on individual resilience, systemic disadvantage is obscured. Disaster scholars here must also reckon with the structural violence of colonisation. Aotearoa New Zealand has a unique hazard profile, and it has unique social infrastructures that can help deal with them. The best disaster mitigation and recovery programmes are inclusive and equity driven. Greater attention to Indigenous Knowledge – Mātauranga Māori – and Indigenous institutions, such as marae and the myriad relationships and connections that such institutions support, might potentially play a crucial role in future disaster mitigation and response.Glossary of Māori words: Aotearoa: New Zealand; Awa: stream, River; Hapū: a division of people, Community; Iwi: tribe; Mātauranga Māori: Indigenous knowledge; Kāinga: home; Manaakitanga: respect and care for others; Marae: communal and sacred facility; Ōtautahi: Christchurch; Raupatu: conquest and confiscation; Rohe: home territory; Rongomau Taketake: Indigenous Rights Governance Partner; Tairāwhiti: Gisborne district; Te Kāhui Tika Tangata: Human Rights Commission; Te Tari Taiwhenua: Department of Internal Affairs; Te Tiriti: The Treaty (of Waitangi); Tiko; Poo; Tino rangatiratanga: self-determination; Tupuna: ancestor; Urupā, Cemetary; Whakapapa: descent, Geneaology, Lineage; Whakawhānaungatanga: the practice of establishing, Maintaining and nurturing relationships; Whenua: land